LAND REFORM IN THE CONTEXT OF DEVOLUTION: LESSONS FROM KAJIADO COUNTY, KENYA - Everlyne Komba; Kenneth Victor Odary; Ali Letura (African Journal on Land Policy and Geospatial Sciences, 2018)
Kenya’s development context is greatly influenced by land use and ownership. Consequently land holds immense cultural, spiritual and socio-political significance for nearly all communities. However, proper utilization of land has been besmirched by numerous challenges. Vulnerable and marginalized groups such as women, children and youth have borne the brunt of land challenges. The Constitution of Kenya, 2010 in appreciation of these complex dynamics has sought to provide a blue print for the realization of land reforms. It is in this regard, that the County Government of Kajiado drawing on its devolved mandate undertook key land reform measures. Applying the criteria of subsidiarity and consensus, Kajiado County realized homegrown policy solution to land challenges. Alongside, useful lessons worth learning such as the importance of harnessing local political capital; involvement of diverse community voices; creation of spaces to entrench global good practice as well as working with and through legitimate structures emerged.